Pengaruh Manajemen Risiko dan Tata Kelola Perusahaan terhadap Kinerja Perbankan (Riwayat: Educational Journal of History and Humanities, 2026)
This study investigates the effect of risk management and corporate governance on banking performance. The research is motivated by the increasing exposure of banking institutions to various financial and operational risks, as well as the crucial role of sound governance in maintaining stability and performance in the banking sector. The objective of this study is to analyze the direct influence of risk management and corporate governance on bank performance. This research employs a quantitative approach using secondary data derived from published annual reports of banking companies. The sample is selected through purposive sampling based on data availability and research criteria. Data analysis is conducted using Partial Least Squares Structural Equation Modeling with the WarpPLS application, which allows for the assessment of both measurement and structural models. The findings reveal that risk management has a positive and significant effect on banking performance, indicating that effective risk identification, assessment, and control contribute to improved operational efficiency and financial outcomes. Corporate governance also demonstrates a positive influence on banking performance, reflecting that transparency, accountability, and effective supervisory mechanisms enhance managerial effectiveness and stakeholder confidence. Furthermore, the results show that risk management and corporate governance jointly play an important role in strengthening banking performance.